A Novel High-Voltage-Cable Stripping Robot - Jun Zhong; Wenxu Ai; Zhichao Wang; Shaoguang Hu; Hongshuang Zhang (Actuators, 2023)
One of the primary duties in the regular maintenance of electrical distribution networks is the cable stripping operation. In this paper, a unique robot is proposed to overcome drawbacks of the conventional manual operation of cable stripping, such as poor efficiency, low safety, and high labor intensity. This innovative cable-stripping robot is made up of a rotating mechanism, a cable gripping component, and a cutter feeding mechanism that can be adjusted depending on the working environment and workload. The robot’s motors, sensors, main control chip, and wireless communication modules are all carefully selected. A carefully designed cascade controller is created for the robot in an effort to lessen damage to the aluminum core. While the outside location loop uses the PID algorithm, the inner speed control loop uses fuzzy PID. The robot can successfully accomplish cable stripping work and demonstrates its potential to reduce labor intensity. Cable stripping experiments are conducted to validate the effect of the robot and its controller.